Mismatch in cerebral blood flow and glucose metabolism after the forced swim stress in rats. Issue 6 (20th June 2016) - Kameno, Yosuke; Suzuki, Katsuaki; Takagai, Shu; Iwata, Keiko; Matsuzaki, Hideo; Takahashi, Kenji; Wakuda, Tomoyasu; Iwata, Yasuhide; Magata, Yasuhiro; Mori, Norio
Abstract : Objective: Neuroimaging studies of depression considered as a stress-related disorder have shown uncoupling in regional cerebral blood flow (rCBF) and regional cerebral metabolic rate for glucose (rCMRglc). We hypothesised that the mismatch change of rCBF and rCMRglc could be a stress-related phenomenon. Methods: We exposed male rats to 15-min period of forced swim (FS), followed by the measurement of rCBF using N -isopropyl-4-[ 123 I] iodoamphetamine ( 123 I-IMP) and rCMRglc using 2-deoxy-2-[ 18 F] fluoro-D-glucose ( 18 F-FDG). Results: The uptake rate of 18 F-FDG in the FS group showed a significant decrease in the prefrontal cortex (0.86±0.20%ID/g, p <0.01) and thalamus (0.77±0.17%ID/g, p <0.05) and tended to be lower in the hippocampus (0.58±0.13%ID/g) and cerebellum (0.59±0.13%ID/g) without overt alteration in the uptake rate of 123 I-IMP. Conclusions: The FS stress can cause mismatch change of rCBF and rCMRglc, which reflect a stress-related phenomenon.